Culture stimuly - Abdul Razak, Mariatulqabtiah (Universiti Putra Malaysia Press, 2015)
People manifest beliefs, beliefs represent culture. Culture of certain comunities, or even from one generation to the next, defines the originality or character of people of the world. Accumulation of knowledge, experience, language, attitudes, religion, values, hierarchies and material objects distinguishes one group of people from another. Influencing stimulus can be many, including observation of natural ecological and environmental factors, particularly from species of animal and plant, or even the advancement of technology by time.